2017
DOI: 10.1186/s40792-017-0350-y
|View full text |Cite
|
Sign up to set email alerts
|

A fascia lata free flap in pelvic exenteration for Fournier gangrene due to advanced rectal cancer: a case report

Abstract: BackgroundFournier gangrene due to advanced rectal cancer is a rapidly progressive gangrene of the perineum and buttocks. Emergency surgical debridement of necrotic tissue is crucial, and secondary surgery to resect tumors is necessary for wound healing. However, pelvic exenteration damages the pelvic floor, increasing the likelihood of herniation of internal organs into the infectious wound. The management of pelvic exenteration for rectal cancer with Fournier gangrene has not yet been established. We herein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Over 83% (5/6) of patients who did undergo DRE demonstrated positive findings, including a palpable mass (4), purulent anal drainage (1), and pain out of proportion (1). This over 80% rate of positive findings on DRE is consistent with a study by the World Journal of Gastroenterology in 2015 which showed that preoperative DRE resulted in positive findings in 75% of FG with underlying rectal cancer and it highlights the importance of including a thorough anorectal examination in all patients with FG [ 1 , 3 , 15 - 17 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Over 83% (5/6) of patients who did undergo DRE demonstrated positive findings, including a palpable mass (4), purulent anal drainage (1), and pain out of proportion (1). This over 80% rate of positive findings on DRE is consistent with a study by the World Journal of Gastroenterology in 2015 which showed that preoperative DRE resulted in positive findings in 75% of FG with underlying rectal cancer and it highlights the importance of including a thorough anorectal examination in all patients with FG [ 1 , 3 , 15 - 17 ].…”
Section: Discussionsupporting
confidence: 88%
“…It is included in many medical calculator applications and includes the measurement of CRP, hemoglobin, white blood cell count, serum sodium, creatinine, and blood glucose level. Scores of ≥6 raise the suspicion for necrotizing fasciitis/FG and scores of ≥8 are strongly predictive of the disease [5,17]. Initial studies of the LRINEC score showed a 92% positive predictive value in diagnosing FG but subsequent studies have questioned its utility [19].…”
Section: Diagnosismentioning
confidence: 99%
“…Fournier's Gangrene is a rare 11 condition marked by fluminent polymicrobial necrotising fasciitis [1][2][3][4][5][6][7][8][9][10] , which is generally localised disease of scrotum or penis or both with occasional extention up to the abdominal wall 11 . In literature many terms have been used synonymously to describe the condition which include idiopathic gangrene of the scrotum, periurethralphelgmon, streptococcal scrotal gangrene and cenegesiticnecrotising cellulitis.…”
Section: Discussionmentioning
confidence: 99%
“…Fournier's Gangrene is a serious surgical emergency condition which involves scrotum or penis or both with occasional extension upto the abdominal wall (3,23) . This clinical condition was first described by GeanAlfered Fournier, A French Dermatologist and Venereologist reported five cases in 1882 3,6 . The hallmark of FG is intense pain and tenderness in the genitalia.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation